Polariton dispersion dependence on concentration of admixture in imperfect superlattice of coupled microresonators - Alodjants, A.P.; Rumyantsev, V.V.; Fedorov, S.A.; Proskurenko, M.V. (Functional Materials, 2014)
Based on the representations of the ideal of photonic structures, the non-ideal systems of this class - polaritonic crystal, which is a set of spatially ordered cavities containing atomic clusters, is considered in the paper. Moreover, the spatial distribution of cavities (resonators) is translation invariant, and the atomic subsystem has randomly distributed defects: impurity atomic clusters (quantum dots) or a vacancies. Numerical modeling of dependence of the dispersion of polaritons in this imperfect superlattice of associated microresonators on impurity concentration is completed. Using the virtual crystal approximation the analytical expressions for polaritonic frequencies, effective mass and group velocities, as a function of corresponding quantum dots and vacancies concentrations, is obtained.